2010
DOI: 10.1128/mcb.00302-10
|View full text |Cite
|
Sign up to set email alerts
|

KLF3 Regulates Muscle-Specific Gene Expression and Synergizes with Serum Response Factor on KLF Binding Sites

Abstract: This study identifies KLF3 as a transcriptional regulator of muscle genes and reveals a novel synergistic interaction between KLF3 and serum response factor (SRF). Using quantitative proteomics, KLF3 was identified as one of several candidate factors that recognize the MPEX control element in the Muscle creatine kinase (MCK) promoter. Chromatin immunoprecipitation analysis indicated that KLF3 is enriched at many muscle gene promoters (MCK, Myosin heavy chain IIa, Six4, Calcium channel receptor ␣-1, and Skeleta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
49
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 68 publications
0
49
0
2
Order By: Relevance
“…KLF3 has also recently been identified as a transcriptional regulator of skeletal muscle differentiation (28). This report showed that KLF3 expression increases during skeletal myocyte differentiation and a proteomics screen found KLF3 enriched at the muscle creatine kinase promoter (MCK).…”
Section: Klf3 and Muscle Cell Biologymentioning
confidence: 87%
See 1 more Smart Citation
“…KLF3 has also recently been identified as a transcriptional regulator of skeletal muscle differentiation (28). This report showed that KLF3 expression increases during skeletal myocyte differentiation and a proteomics screen found KLF3 enriched at the muscle creatine kinase promoter (MCK).…”
Section: Klf3 and Muscle Cell Biologymentioning
confidence: 87%
“…Further understanding will be dependent on defining the FHL3-binding motif and examining changes in gene expression in KLF3 null cell lines, rescued with KLF3 protein in which this site has been mutated. The high level of expression of FHL3 in skeletal and cardiac muscle and recent reports linking KLF3 with muscle cell growth and differentiation (28,29), hints that common targets may be found in this tissue. Apart from the conserved CtBP-binding motif, KLF3 shares little N-terminal homology with KLF8 and KLF12, suggesting that the association with FHL3 may not be shared with KLF3's most closely related family members.…”
Section: Protein Partners Of Klf3mentioning
confidence: 99%
“…in certain contexts it can function as an activator (15,16). Its hematopoietic role has not been fully characterized, although it is known to be a direct target gene of the erythroid factor Klf1 (17).…”
mentioning
confidence: 99%
“…The transcription factor SRF physically associates and synergizes with KLF3, thereby working as a transactivation complex, as shown for a muscle-specific target gene (12). Furthermore, mice in which SRF was deleted in B cells show a loss of MZ B cells (63), a phenotype shared with KLF3-deficient mice (7,9).…”
Section: Srf Is Irrelevant Both For Klf3 Repressing B 7 and Driving Mmentioning
confidence: 85%
“…Indeed, KLF3 has been shown to interact with the common transcriptional corepressors C-terminal binding protein 2 (CtBP2) and four and a half LIM domain protein 3 (FHL3) (8,10,11). A further KLF3-interacting transcription factor is serum response factor (SRF), as identified in muscle cells (12). Thus, KLF3 may act exclusively in concert with other transcriptional regulators.…”
mentioning
confidence: 99%